Correlação entre citotoxicidade, alterações cromossômicas e atividade antibacteriana de compostos triazenos em células de medula óssea - Rodrigues, Jacqueline Nunes (2013)
Leukemias are a heterogeneous group of hematologic malignancies. The treatment of these neoplasms has been a challenge to the scientific community due to genetic diversity in leukemic cells. Acquired chromosomal abnormalities as well as modifications of gene expression are involved in the genesis of leukemia. Such facts have increased interest in the development of new effective chemotherapeutic agents that reach specific molecular targets. The compounds of the triazene class like dacarbazine and temozolomide have been used in the clinical treatment of various cancer types, including melanoma, leukemia and glioma. Two new compounds triazenes complexed with copper (CuII) were synthesized to identify new agents with antiproliferative and antibacterial activity. The Compounds 1 - Bis [ 1,3-bis (2-chlorofenyl) triazenido-N11,N13--O-methoxy-pyridine-N-copper(II)] - C36H34N8O2Cl4Cu2 and 2 - Bis [1,3-bis (2-fluorfenyl) triazenido-N11,N13--O-hidroxy-pyridine-N-copper(II)]-C34H28N8O2F4Cu2 were tested in leukaemic cells from AML, ALL, CML and MDS in vitro by MTT colorimetric assay. A higher-capacity of antiproliferative was verified in compound 1 with cytotoxicity (IC50: 3.8 to 28.6 μM) in most cell types at diagnosis, particularly in cells with chromosome abnormalities. This compound also showed in vitro cytotoxicity of relapse of ALL cells with karyotypic alterations. The cytotoxic activity was significantly higher in leukemic cells than in normal cells. The MIC values showed that compound 1 had higher activity than compound 2, showing narrow spectrum antibacterial activity against gram positive ATCCs and multiresistant bacterial strains. It was observed that Compound 1 was more promising in relation to the antiproliferative potential than the antimicrobial activity, even when compared to antineoplastic agents such as etoposide. Additional studies to understand the mechanism of action will soon be developed.